Development and Validation of RP-HPLC Method for Simultaneous Estimation of Cyclosporine A in Combination with α-Linolenic Acid - P. Phadatare, Suvarna; Momin, Munira; Pimplikar, Pramod; Sirwani, Rajesh (Asian Journal of Chemistry, 2022)
A suitable isocratic reverse-phase HPLC method was developed for the simultaneous estimation of cyclosporine A and α-linolenic acid (ALA) in their synthetic mixture formulated to evaluate the synergistic therapeutic effect. The reversed phase HPLC chromatographic method was developed to obtain two separate peaks within short retention time period (30 min run time), without any interference from excipients peaks. The chromatographic separation was achieved on C18 column (5 μm, 4.6 × 250 mm) at 50 ± 0.3 ºC. The analytes were eluted at a flow rate of 0.8 mL/min using ultraviolet detector at 210 nm with mobile phase of 1% v/v orthophosphoric acid in water: acetonitrile:2-propanol (25:60:25 v/v/v). The proposed method was validated for specificity, precision, linearity, accuracy and system suitability. All validation parameters were within the acceptable range.